101. Who Does Not Show up for Followup in an HIV Prep Clinic?. (31st December 2020) - Williams, Robert; Flanigan, Timothy P; Bazerman, Lauri; Tao, Jun; Chu, Christina; Silva, Elizabeth S; Almonte, Alexi; Montgomery, Madeline; Chan, Philip
Abstract: Background: Understanding real-life HIV pre-exposure prophylaxis (PrEP) care is key to address HIV infection. An HIV PrEP clinic was started in Providence, RI in 2013, performing outreach to men who have sex with men (MSM) and other high-risk individuals. Our prior clinical studies and other literature have shown that many high-risk patients do not return for followup PrEP visits. We sought to better identify correlates of patients who were lost to follow up (LTFU), with implications for improving PrEP care retention. Methods: Data was collected from all cis-gender patients who first presented to the RI PrEP Clinic from 2013 to mid-2019. Correlations in demographic information and behaviors related to PrEP care were demonstrated through descriptive analysis. A multivariate analysis was then performed to elucidate possible predictors. LTFU was defined as having no subsequent visit within six months of the initial appointment after being prescribed PrEP. Results: Of 570 patients, most identified as male (96%), White (65%), and non-Hispanic (82%). 65% of patients made one followup appointment within six months of intake, and 35% were LTFU. The following characteristics correlated with higher rates of LTFU: being below 25 years of age (17% vs 27%; p=0.002), illicit drug use (42% vs 53%; p=0.02), and having both same and opposite-sex partners (7% vs 16%). Characteristics which correlated with lower rates of LTFU included only having same-sex partners (88% vs 74%; p< 0.001), alcohol use (86% vs 80%; p=0.04), and bachelor's degree completion (71% vs 49%; p< 0.001). Race, gender, and risk behavior showed no correlation. Conclusion: A clear understanding of mechanisms of retention is high priority for forming care protocol interventions. Given trends with age, education, and PrEP indication, targeted interventions are needed to improve retention in HIV PrEP care and reduce incidence in at-risk communities. Disclosures: All Authors : No reported disclosures